Análise citológica da mucosa oral e concentrações salivares e urinárias de 1-hidroxipireno glucoronídeo em tomadores de chimarrão - Cândido, Lisiane (2015)
Carcinogenesis is a complex multifactorial process dependent on inherent to individual or environmental factors. Environmental polycyclic aromatic hydrocarbons (PAHs) have been pointed as a risk factor for different types of cancer, especially in upper aerodigestive tract. Chimarrão is a hot maté beverage containing PAHs that are incorporated to the herb during drying process of the leaves. Individuals that drink chimarrão are exposed do PAHs, which can be assessed by 1-hydroxypyrene-glucuronide levels (1-OHPG). The aim of the present study was to evaluate cytomorphometric alterations of oral mucosa epithelium in chimarrão drinkers correlating them to salivary and urinary levels of 1-OHPG. Adult males and females without history of regular alcohol use were allocated into 4 groups: (1)=39 chimarrão drinkers who did not smoke; (2)=25 chimarrão drinkers who smoked; (3)=27 smokers who did not drink chimarrão; and (4)=27 individuals who had neither of these habits. Mucosal scrapings were performed and subjected to qualitative (Papanicolaou) and quantitative (nuclear area, cytoplasmic area, nucleus/cytoplasm ratio) analysis. Urine and saliva samples were assayed for 1-OHPG by high-performance liquid chromatography (HPLC). All samples were classified into Papanicolaou class I. Nuclear and cytoplasmic areas of epithelial cells in soft palate smears did not significantly differ between the groups, whereas in buccal (cheek) mucosa they were significantly greater in the chimarrão group than in controls. The nucleus/cytoplasm ratio as well as salivary and urinary concentrations of 1-OHPG did not significantly differ. Urinary and salivary 1-OHPG concentrations were positively correlated to each other but they did not show any correlation with the cytometric variables. Nuclear and cytoplasmic areas were positively correlated to each other in either palate or buccal mucosa smears. Conclusion : Chimarrão was associated with neither cytomorphometric alterations in epithelial cells of palate smears nor urinary and salivary 1-OHPG levels. Buccal smears showed higher nuclear and cytoplasmic area in the chimarrão group, but this result does not support an association with dysplasia.